Menyingkap dua hari tergelap di tahun 1965 : melihat peristiwa G30S dari perspektif lain - Luhulima, James (Jakarta : Penerbit Buku Kompas, 2006)
Political conditions in Jakarta, the days before and after the abortive 1965 Coup d'etat
Includes bibliographical references (p. 201-203) and index
Keywords: Soekarno, -- 1901-1970.; Gerakan Tigapuluh September; Partai Komunis Indonesia; Indonesia -- Politics and government -- 1950-1966; Indonesia -- History -- Coup d'etat, 1965